A BRIEF DESCRIPTION OF THE CATSHARK, CHILOSCYLLWM GRISEUM MULLER AND HENLE, FROM INDIAN WATERS, WITH SOME BIOLOGICAL NOTES - Devadoss, P (Indian Journal of Fisheries, 2011)
The cat shark, Chfloscyllium griseum, is described in detail based on samplescollected frcm both the coasts of India. The patterns of growth of individual organsare also given. The length-weight relationship was not significantly different betweensexes, so a common value, Log W = —4.8378 + 2.7314 log L, was obtained.The shnrk feeds on bottom fishes. Males mature at 520 mm and females at 530 mmTL. The egg-cases are laid outside for development.